2018
DOI: 10.1021/acs.joc.8b03057
|View full text |Cite|
|
Sign up to set email alerts
|

Short Total Synthesis of Δ12-Prostaglandin J2 and Related Prostaglandins. Design, Synthesis, and Biological Evaluation of Macrocyclic Δ12-Prostaglandin J2 Analogues

Abstract: Comprised of a large collection of structurally diverse molecules, the prostaglandins exhibit a wide range of biological properties. Among them are Δ 12 -prostaglandin J 2 (Δ 12 -PGJ 2 ) and Δ 12 -prostaglandin J 3 (Δ 12 -PGJ 3 ), whose unusual structural motifs and potent cytotoxicities present unique opportunities for chemical and biological investigations. Herein, we report a short olefin-metathesis-based total synthesis of Δ 12 -PGJ 2 and its application to the construction of a series of designed analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…2 This type of prostaglandin possesses an interesting biological profile and attempts to explore how the structure of this compound affects its activity are hampered because it is not amenable to ready synthetic divergence from an advanced intermediate. [3][4][5][6][7][8][9][10] In relation to this point, we demonstrated that incorporation of a nitrogen atom at the 4-position in the cyclopentenone enabled ready modification of the α-prostanoid side chain. 2 In addition, alkylidination/arylidination was successfully used to instal the unsaturated exocyclic side chain present in the natural product analogue 1.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…2 This type of prostaglandin possesses an interesting biological profile and attempts to explore how the structure of this compound affects its activity are hampered because it is not amenable to ready synthetic divergence from an advanced intermediate. [3][4][5][6][7][8][9][10] In relation to this point, we demonstrated that incorporation of a nitrogen atom at the 4-position in the cyclopentenone enabled ready modification of the α-prostanoid side chain. 2 In addition, alkylidination/arylidination was successfully used to instal the unsaturated exocyclic side chain present in the natural product analogue 1.…”
Section: Introductionmentioning
confidence: 78%
“…The solution was stirred at room temperature for 1 h. After this time, the reaction mixture was concentrated under a flow of air, and the resulting residue was purified by column chromatography (c-Hex/EtOAc; 1:1), affording the desired product 9 (308 mg, 87%) as a white solid, with data as reported. 26 1H NMR (400 MHz, CDCl 3 ): δ 1.65 (dt, J = 14.5, 4.0 Hz, 1H, CH 2 ), 2.05 (s, 3H, CH 3 ), 2.81 (dt, J = 14.5, 7.5 Hz, 1H, CH 2 ), 4.69-4.75 (m, 1H, CH), 5.46-5.53 (m, 1H, CH), 5.98 (ddd, J = 5.5, 2.0, 1.0 Hz, 1H, CH), 6.08-6.15 (m, 1H, CH) ppm; 13 Di-tert-butyl[(1S,4R)-4-acetoxycyclopent-2en-1-yl]imidodicarboxylate (10) Alcohol 9 (0.29 g, 2.04 mmol, 1.0 equiv.) was added to a solution of triphenylphosphine (1.59 g, 6.05 mmol, 3.0 equiv.)…”
Section: (1r4s)-4-hydroxycyclopent-2-en-1-yl Acetate (9)mentioning
confidence: 99%
“…174 Prompted by these reports, we developed a short and practical synthesis of the natural product and numerous of its designed analogues leading to identification of potent antitumor agents, [175][176][177] including the monomeric and dimeric macrolactones as shown in Figure 16e. 178 Numerous other total synthesis endeavors in our laboratories directed toward antitumor natural products were also extended to the design, synthesis, and biological evaluation of analogues of the target molecule as summarized in Figure 16. Included among them are paclitaxel (9, Figure 16f,g), 179,180 rapamycin (8, Figure 16h), 181 sarcodictyins A and B (315 and 316, Figure 16i), 182 epothilones A and B (318 and 11, Figure 16j), 183,184 and cortistatin A (25, Figure 16n), 185 with a number of interesting compounds emerging as biological tools and potential drug candidates.…”
Section: Synthesizing Molecules For Biology and Medicinementioning
confidence: 99%
“…For example, 1,15-lactone Δ 12 -PGJ 2 1 is among the most promising cyPGs in the screening against NCI-60 tumor cell lines. [7] 15-Deoxy-Δ 12,14 -PGJ 2 2 is known as a selective ligand for PPAR γ nucleus receptors responsible for gene transcription, modulation of inflammatory processes and apoptosis, hypertension, and other functions of the cell nucleus. [8] Unlike the majority of proinflammatory agents, PG 15-deoxy-~12,14 PGJ 2 2 exhibits anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%